Internet use, political and civic participation among marginalized youths - Samsuddin, Jamali; Lai, Che Ching; Hasan, Hamisah; Zamri Ahmad, Abd Mua'ti (Universiti Putra Malaysia, 2019)
Youth political apathy is a global phenomenon that threatens democracies around the world, including Malaysia. The mobilization theory suggests that new communication technologies such as the Internet could increase participation, especially underprivileged group. This quantitative study surveyed marginalized Malay youths in the central region to examine: (i) the level of their Internet use; (ii) the level of their political and civic participation; and (iii) the mediating effect of civic engagement in the relationship between Internet use and political participation. The data were obtained through a questionnaire completed by 400 youths aged 15 to 25 years old living in urban poor areas within the Klang Valley. The results show that their Internet use was still confined to basic activities; their political and civic participation was low; and there was a weak positive relationship between Internet use and participation. Civic participation partially mediated the effect of Internet use on political participation. Future efforts to lure young people back into the political socialization process must be mediated over time by civic participation. Enhancement of Internet skills and early exposure to civic activities will likely bode well for their future political action.